For a semiotic analysis of culture through the logo of Algerian niversities - BELAZREG, Nassima; NOUADRI, Samia Ilhem (The Notebooks of the Algerian Poetics Laboratory Journal, 2022)
this study, we are interested in the logos of Algerian universities because we believe that they are a relevant means of communication in the era of globalization and new technologies. Through this contribution, we first want to define the term "logo" and address the principles of its design. Then, we will try to carry out an overview of the work in semiotics. Because, we consider that the logo is a means of communication carrying meaning. Then, we will present our corpus made up of some logos of Algerian universities and we will talk about the participation of other historical and cultural signs in the transmission of the message.